2002
DOI: 10.1007/s11663-002-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic study of MnO-SiO2-Al2O3 slag system: Liquidus lines and activities of MnO at 1823 K

Abstract: The liquid MnO-SiO 2 -Al 2 O 3 system was studied at 1823 K by equilibrating MnO-SiO 2 -Al 2 O 3 melts of different compositions with Pt-Mn alloys and an oxygen-bearing gas phase. Liquid compositions for cristobalite saturation were determined at 1823 K. A new liquidus for the cristobalite primary field is proposed. The activity of Mn in the Pt-Mn alloy at 1823 K can be represented by the following equation:The MnO activity was measured in different melt compositions, and MnO isoactivity lines were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…From the experimental data shown in the Figure 1, it is also shown that, for the c MnO(s) in Al 2 O 3 -containing systems, the effect of Al 2 O 3 on the c MnO(s) is not remarkable in the range of concentration investigated in the present study as well as in the work of Woo et al [13] The c MnO(s) is plotted as a function of concentration of AlO 1.5 in Figure 2 Figures 1 and 2, it is not so certain whether the presence of MnS affects the c MnO(s) or not. From the experimental data obtained in the present study, c MnO(s) in the liquid oxysulfide seems a bit higher than that in liquid oxide without sulfur, within experimental scatters.…”
Section: A Activity Of Mn (A Mn ) In Pt-mn Alloysupporting
confidence: 68%
See 2 more Smart Citations
“…From the experimental data shown in the Figure 1, it is also shown that, for the c MnO(s) in Al 2 O 3 -containing systems, the effect of Al 2 O 3 on the c MnO(s) is not remarkable in the range of concentration investigated in the present study as well as in the work of Woo et al [13] The c MnO(s) is plotted as a function of concentration of AlO 1.5 in Figure 2 Figures 1 and 2, it is not so certain whether the presence of MnS affects the c MnO(s) or not. From the experimental data obtained in the present study, c MnO(s) in the liquid oxysulfide seems a bit higher than that in liquid oxide without sulfur, within experimental scatters.…”
Section: A Activity Of Mn (A Mn ) In Pt-mn Alloysupporting
confidence: 68%
“…In a previous investigation, [13] however, the latter chemical removal did not produce a big difference in the Mn concentration of Pt-Mn alloy. After the pretreatment, Mn concentrations were measured by the inductively coupled plasma (ICP) method after the alloy was completely dissolved in the acid (HCl 14 mL + HNO 3 6 mL), whereas heat was applied.…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…CaO may also come from interaction of the molten steel reacts with CaO-based top slag in a ladle or tundish. Many experimental studies [1][2][3][4][5][6][7][8] have been performed on MnO-Al 2 O 3 -SiO 2 inclusion systems. In addition, several thermodynamic calculations, [9][10][11][12][13][14][15][16][17] simply based on the activity of slag and interaction parameters of alloying elements (such as Mn, Si, Al and O) in steel, have been conducted in order to help control MnO-Al 2 O 3 -SiO 2 type of inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…This has recently been confirmed by MnO-activity measurements in the MnO-SiO 2 -Al 2 O 3 system. [41] The cell model, on the other hand, is unable to describe correctly phase equilibria in the area of mullite saturation. However, since the low MnO region is essential for simulations related to the silicomanganese smelting process, and since phase equilibria in the area of mullite saturation are relatively unimportant for both high carbon ferromanganese slags and silicomanganese slags, it has been decided to use the cell model [12,13,14] in this work.…”
Section: Introductionmentioning
confidence: 99%